2020
DOI: 10.3390/su12041613
|View full text |Cite
|
Sign up to set email alerts
|

A Planning Support Tool for Layout Integral Optimization of Urban Blue–Green Infrastructure

Abstract: Urban blue infrastructure (UBI) and urban green infrastructure (UGI) can be seen as an integrated system in which services and spatial layouts complement each other. However, given its complexity, it is difficult to integrate and optimize the layout of urban blue and green infrastructure (UBGI) in the built environment. This study develops a planning support tool for the layout integral optimization (PSTLIO) of UBGI. Using Hekou City in China as a case study, service demands and the supply of suitable land for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Specifically, the model is designed to investigate an index score of variables for various characteristics and scales, suggesting the analytical potential to represent the overall well-being state of the city and the availability of GI location choices in a sustainable urban space. Existing GI studies mainly considered geographic and topographic characteristics as key variables [26][27][28][29][30]. In this study, however, publicly accessible descriptive variables-i.e., demographic, climate, environment, and form-specific GI variables-were considered together to enable the overall efficiency improvement of urban elements, including residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the model is designed to investigate an index score of variables for various characteristics and scales, suggesting the analytical potential to represent the overall well-being state of the city and the availability of GI location choices in a sustainable urban space. Existing GI studies mainly considered geographic and topographic characteristics as key variables [26][27][28][29][30]. In this study, however, publicly accessible descriptive variables-i.e., demographic, climate, environment, and form-specific GI variables-were considered together to enable the overall efficiency improvement of urban elements, including residents.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and Oh [28] developed the GI location assessment system based on geographical information for Namyangju-si, Korea, and attempted the landscape ecological evaluation from both macro and micro perspectives. Zhou and Wu [29] attempted to distribute the Green Land of Hekou City, China, by matching the demand for rust and topographical characteristics. Lai et al [30] identified the relationship between land use and spatial identification by presenting a plan to implement GIs in three areas near Cagliari, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the site space was comprehensively considered and effective planning principles for urban park space were proposed. In addition to service demand and suitability, existing green spaces were given priority [ 36 ]. The selection of impact factors was based on the study of the soundscape, according to four impact factors—plant density, site elevation, degree of structural enclosure, and functional mixing degree.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, geographic information system (GIS) technology was used. GIS represents a convenient digital system to collect and compare spatial and geographical data, and has increasingly been used in spatial decision support systems [33,34]. In the past few years, GIS has emerged as a powerful risk assessment tool, in particular to assess risks from natural hazards.…”
Section: Work Aims and Research Approachmentioning
confidence: 99%